AB0496 Segmental evaluation of joint limitations in scleroderma - prospective monocentric study. (23rd January 2014) - Ricard, E.; Verdier-Kessler, C; Sparsa, A; Vergne-Salle, P; Doeffoel-Hanzt, V; Bonnet, C.; Dufauret-Lombard, C.; Bertin, P.; Fauchais, AL
Abstract : Background: A multidimensional assessment is essential to establish the rehabilitation program in patients with scleroderma in order to limit functional disability. In fact, scleroderma is responsible for unfunctionality of the hand in 38% of the limited forms and 64% of the diffuse forms, linked to cutaneous and periarticular fibrosis, Raynaud's phenomenon and digital ulcers. Objectives: Methods: We prospectively studied the joints limitation of the hand and other joints in 39 patients with scleroderma at a multidisciplinary consultation. Rodnan score, Health Assessment Questionnaire score (HAQ) and hand functional indice of Cochin were systematically performed. Results: Among the 39 patients, 29 had a limited form. The average age was 58.2 ± 13.9 years and mean disease duration was 6.6 ± 6.1 years. Rodnan score averaged 8.2 ± 8.2, HAQ 1.12 ± 0.818 and the hand scale of the Cochin 24 ± 22. 23 patients (59%) complained of joint pain (mean EVA score 3.6, range 0.5 to 8). We observed a limitation of joints' hand in 69% of patients (n = 27) with an average number of limited joints of 1.5 ± 3.4 for the metacarpophalangeal (MCP), 3.8 ± 4.5 for proximal interphalangeal joints (PIP) and 3.1 ± 3.8 for the distal interphalangeal joints (DIP). The pulp-palm distance is higher than zero in 44% of cases. Limitations of joints of the hand affect autonomy (hand Cochin and HAQ, p <0.05) and appeared independent of age, duration of Raynaud development and scleroderma or the existence of previous digital ulcerations. Patients with diffuse scleroderma are characterized by increased difficulties in closing the hand (number of fingers with a distance pulpo-palmar non zero 4.3 ± 3.2 vs 0.9 ± 1.8, p = 0.002), reduced range of motion of the MCP (4.2 ± 5 vs. 0.5 ± 1.9, p = 0.002) and limitations of other limb joints (7 ± 3.2 vs. 2.03 ± 2.9, p = 0.0001). Difficulties in closing the hand, limitation of MCP and PIP joints are correlated with the Rodnan score (respectively, p <0.001, p = 0.0159, p = 0.0098). Only limitations DIP joints didn't correlate with Rodnan score. Patients receiving human help at home are also characterized by increased difficulties in closing the hand, a limited number of MCP joints of the dominant hand significantly higher (p <0.05). Conclusions: Joints limitations of the hand in scleroderma are extremely frequent source of disability and appear to be correlated with cutaneous sclerosis. A early and targeted physiotherapy should be implemented to reduce this handicap. Disclosure of Interest: None Declared